2003
DOI: 10.2133/dmpk.18.128
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Dependent Inhibition Profiles of Fourteen Drugs on CYP3A4 Activity Measured by A High Throughput LCMS/MS Method with Four Probe Drugs, Midazolam, Testosterone, Nifedipine and Terfenadine

Abstract: The CYP3A4 enzyme is known for its atypical inhibition kinetics; ligand inhibition can differ depending upon the probe drug used. A high throughput-LCMS/MS CYP3A4 inhibition assay with four substrate drugs was developed to minimize the potential oversight of CYP3A4 inhibition. The assay uses a 96-well format, human liver microsomes, and four CYP3A4 substrate drugs, midazolam, testosterone, nifedipine and terfenadine. After incubation of the individual substrate with human liver microsomes, the reaction is stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 26 publications
(26 reference statements)
6
27
0
Order By: Relevance
“…For example, ketoconazole is more extensively used than itraconazole as a CYP3A index inhibitor, even though both ketoconazole and itraconazole have similar inhibitory potentials against CYP3A-mediated midazolam 19-hydroxylation (IC 50 @ 0.01 mM) (Racha et al, 2003). The reason for this preference is that studies have shown that ketoconazole has a strong inhibitory effect on various CYP3A substrates including midazolam, nifedipine, testosterone, and triazolam (Wang et al, 1999;Perloff et al, 2000;Racha et al, 2003;Greenblatt et al, 2011), while itraconazole has a weak inhibitory effect on CYP3A-mediated terfenadine metabolism (IC 50 . 50 mM) (Racha et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ketoconazole is more extensively used than itraconazole as a CYP3A index inhibitor, even though both ketoconazole and itraconazole have similar inhibitory potentials against CYP3A-mediated midazolam 19-hydroxylation (IC 50 @ 0.01 mM) (Racha et al, 2003). The reason for this preference is that studies have shown that ketoconazole has a strong inhibitory effect on various CYP3A substrates including midazolam, nifedipine, testosterone, and triazolam (Wang et al, 1999;Perloff et al, 2000;Racha et al, 2003;Greenblatt et al, 2011), while itraconazole has a weak inhibitory effect on CYP3A-mediated terfenadine metabolism (IC 50 . 50 mM) (Racha et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In general, P450 index inhibitors used in reaction phenotyping studies should inhibit each P450 isoform-specific activity in a substrate-independent manner. One example is ketoconazole, a representative CYP3A inhibitor that inhibits the CYP3A-mediated metabolism of several substrates including nifedipine, midazolam, terfenadine, testosterone, and triazolam (Wang et al, 1999;Perloff et al, 2000;Racha et al, 2003;Greenblatt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Peak plasma concentrations of cyclosporin A determined in the same study were 1.1 to 1.3 M, in agreement with published data (Min et al, 2000) and above the IC 50 values determined for cyclosporin A in vitro. Unlike rifampicin, cyclosporin A is also a potent inhibitor of CYP3A4, with a K i value in the range of 0.7 to 2 M (Paine et al, 2000;Racha et al, 2003). Therefore, the significantly increased bosentan concentrations in the presence of cyclosporin A may result from a combined effect on hepatic uptake through inhibition of OATP1B1 and OATP1B3 transport together with inhibition of CYP3A4-mediated metabolism.…”
Section: Bosentan Is a Human Oatp Substratementioning
confidence: 99%
“…When incubated with a battery of recombinantly expressed cytochrome P450 enzymes, it appeared that the CYP3A family (CYP3A4 and 3A5) was predominantly involved in the overall metabolism of CJ-13,610. In addition, when coincubated with the potent CYP3A inhibitor ketoconazole, sulfoxidation of CJ-13,610 was inhibited with an estimated IC 50 of 7 nM, closely resembling the inhibitory potency of ketoconazole toward known selective probe substrates of CYP3A4 such as midazolam and testosterone (Racha et al, 2003). With CYP3A being the predominant metabolic pathway, as suggested by our in vitro studies, CJ-13,610 could be at risk for victim drug-drug interactions if coadministered with potent inhibitors of CYP3A4 such as azole antifungals or antimicrobials such as erythromycin.…”
Section: Discussionmentioning
confidence: 79%